Business Development of Print and Photocopy Services in Providing Welfare for Employees from an Islamic Economic Perspective in Terara Village, East Lombok Regency - Putri, Sindya Maretha; Rois, Ihsan (Westscience Press, 2024)
This research aims to determine and analyze the development of the print and photocopy services business in providing welfare for employees from an Islamic economic perspective in Terara Village, East Lombok Regency. This research is descriptive qualitative research. Data collection techniques use interviews, observation and documentation. Determining informants in this study used a purposive technique. The technique for checking the validity of the data used by the author in this study was triangulation. Based on the results of the research that has been carried out, it can be seen that the development of the Print and Photo Copy Services Business is not yet optimal because Handal Computer Printing must re-optimize the implementation of the SWOT analysis so that the Handal Computer Printing business can be more comprehensive in knowing the state of the business being run. Then, if you look at the welfare of the employees in this research, they are prosperous in terms of financial and non-financial welfare.